2020
DOI: 10.3389/fnhum.2020.572693
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Global-Brain Functional Connectivity of the Cerebello-Thalamo-Cortical Network in Patients With Dry Eye Disease

Abstract: Background: The pathophysiology of patients with dry eye disease (DED) is associated with abnormal functional connectivity (FC). The present study aims to probe alterations of voxel-wise brain-wide FC in patient with DED at rest in an unbiased way. Method: A total of 20 patients with DED and 23 controls matched by age, sex, and years of education underwent resting-state functional magnetic resonance imaging scans. Global-brain FC (GFC) was adopted to analyze the images. Support vector machine (SVM) was utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…DE is generally considered to be a corneal disease, but our previous work has shown that some ophthalmologic diseases are accompanied by changes in specific brain areas 5 , 6 , although the nature and significance of this association are unclear. Pan et al used Global-brain FC to analyze the images of 20 dry eye patients and found that the difference in the value of left thalamus can distinguish patients from normal people 7 . The study by Levitt et al also showed that the cause of dry eye pain may be related to abnormal central pain management 8 .…”
Section: Introductionmentioning
confidence: 99%
“…DE is generally considered to be a corneal disease, but our previous work has shown that some ophthalmologic diseases are accompanied by changes in specific brain areas 5 , 6 , although the nature and significance of this association are unclear. Pan et al used Global-brain FC to analyze the images of 20 dry eye patients and found that the difference in the value of left thalamus can distinguish patients from normal people 7 . The study by Levitt et al also showed that the cause of dry eye pain may be related to abnormal central pain management 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, MD values of the right posterior thalamus were significantly different between DE and HC. Pan et al [ 44 ] used the global brain functional connectivity (GFC) method at voxel level to study the differences in functional tissue between DE patients and healthy controls. The GFC changes in the cerebellum-thalamic-cortex network in DE patients may be related to visual impairment and persistent pain symptoms, and reduced GFC may lead to a continuous stress response and reduced pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Although topography machines do not measure the eyelid, its footprint can be seen in the Medmont E300's raw data, where the eyelashes interfere with the topography measurement, resulting in slit-like gaps on the resultant map. Additionally, the eyelid geometry follows the overlayed smoothed-out anterior eye geometry when the eyelid is entirely folded, as appeared in X-ray scans [45] and MRI images [46,47]. As detailed information on how the upper and lower eyelid surfaces interact with and apply pressure to the ocular surface was required, the eyelid's three-dimensional shape was reverseengineered from its footprint extracted from the Medmont E300 raw data.…”
Section: Eyelid Edge Detection and Modellingmentioning
confidence: 99%